Determinan Kelelahan Kerja pada Perawat Ruang Rawat Inap di Rumah Sakit X Pekanbaru - Mufiendra, Dwi Ilna; Muhamadiah, Muhamadiah; Zaman, M Kamali; Santoso, Santoso (LPPM Hang Tuah Pekanbaru, 2024)
Nurses are at high risk on fatigue during working. This fatigue effect can be a danger to patient safety and affect the quality of hospital service. A short survey showed some nurses complained of fatigue symptoms such as decreased concentration, yawning, headache, and fatigue throughout the body. This study aims to analyze the work fatigue of nurses in X Hospital Pekanbaru by analyzing the relationship between working period, lighting, nutritional status, and work shifts as well as the dominant factors that affect work fatigue. This study was quantitative analytic with a cross-sectional design. The sample of this study was 60 people (total sampling). Data analysis using chi-square and logistic regression. The results of this study found that affecting the work fatigue of nurses in X Hospital Pekanbaru was lighting and nutritional status. The dominant factor that influences the work fatigue of nurses is lighting. The hospital is recommended to improve the quality of lighting in the workplace, especially inpatient rooms, with efforts to provide adequate lighting by PERMENKES standard No. 7 in 2019 which is equal to 250 lux.